Copper-Catalyzed Amination of Vinyl Azides to α-Ketoamides - Wang, Yu; Zhang, Dongling; Zhang, Kaining; Liu, Zhenhua; Lin, Jing; Cao, Wei; Fang, Zhongxue (SynOpen, 2019)
An efficient approach for the amination of vinyl azides with N,N-dialkylacylamides has been developed. By using this protocol, structurally important α-ketoamides can be easily synthesized. The key to success is not only the introduction of a Cu(I)/oxygen catalytic system but also the utilization of t-BuOCl and benzoic acid as additives. The reaction is operationally simple, scalable, and displays broad scope and functional group tolerance. A possible mechanism involving copper-catalyzed oxidative generation of peroxide radicals is proposed.
Keywords: amination; α-ketoamide; vinyl azide; copper-catalysis; N,N-dialkylacylamides